Ethanomedicinal Plants and Indigenous Knowledge Systems used by Chaudhari Tribes of Ghodbar Region, Mangrol Taluka, Gujarat - Nikunj Chaudhari; Smit Bhavsar; Nainesh R. Modi (International Journal of Scientific Research in Science and Technology, 2025)
The present study on ethnomedicinal plants which were carried out in the Forests area of Ghodbar village, Mangrol Taluka, Surat District, Gujarat, India. The purpose of the study ethnomedicinal plants was to collect traditional indigenous knowledge about the medicinal plants and their significance. Medicinal plants have been used for ancient times of periods to cure and prevent the wide range diseases. The Chaudhari people of the Ghodbar village, they still used medicinal plants for their daily life to prevent such kind of diseases. The information about the plants was collected from the person who has known the plants, and their uses was called “Bhagat” in the Chaudhari dialect. During this present study 56 plants species was recorded which was used for curing diseases. The recoded plant species was belonging to 31 different families.
Keywords: Medicinal plant; Chaudhari Community; Conservation; Bhagat; Ghodbar forest